2010
DOI: 10.1016/j.jvs.2009.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Trends in vena caval interruption

Abstract: From 1998 to 2005, the estimated rates of prophylactic VCF placement increased at a significantly higher rate than VCF placement in the setting of DVT or PE. Significant increases in the use of prophylactic VCFs were seen in the setting of morbid obesity and head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…37 While newer treatments for pulmonary embolism, such as dabigatran, may be as effective but somewhat safer than warfarin, 38 these agents are not yet standard of care. In addition to the harms of anticoagulation, IVC filters, which are increasingly used in the management of pulmonary embolism, 39 can cause substantial morbidity, both during insertion (e.g., bleeding) and while in place (e.g., clotting of filter, fracture and migration of filter, increased incidence of subsequent deep vein thrombosis). 40,41 As use of CT scans continues to rise, 5 the problem of overdiagnosis and overtreatment of pulmonary embolism will likely continue to grow.…”
Section: Commentmentioning
confidence: 99%
“…37 While newer treatments for pulmonary embolism, such as dabigatran, may be as effective but somewhat safer than warfarin, 38 these agents are not yet standard of care. In addition to the harms of anticoagulation, IVC filters, which are increasingly used in the management of pulmonary embolism, 39 can cause substantial morbidity, both during insertion (e.g., bleeding) and while in place (e.g., clotting of filter, fracture and migration of filter, increased incidence of subsequent deep vein thrombosis). 40,41 As use of CT scans continues to rise, 5 the problem of overdiagnosis and overtreatment of pulmonary embolism will likely continue to grow.…”
Section: Commentmentioning
confidence: 99%
“…1,2 The absolute indications for placement include proximal DVTor PE with contraindications for anticoagulation, or PE while on anticoagulation, as indicated by several guideline bodies. 3e5 The recommendations, though, are conflicting for IVC filter use in trauma patients or patients undergoing major surgery who are unable to undergo pharmacologic prophylaxis, with the most updated ninth American College of Chest Physicians (ACCP) guidelines 3 recommending against IVC filter use, and the Eastern Association for the Surgery of Trauma (EAST) 4 and the Society for Interventional Radiology 5 advocating placement of IVC filters.…”
Section: Introductionmentioning
confidence: 99%
“…This has coincided with an increase in the use of filters, with the highest increase observed for prophylactic indications. 1,2 The increase in retrievable IVC filters has not been mirrored, however, in an increase in the rate of retrieval, although data have been difficult to capture owing to the diverse range of specialties and populations in whom these devices are placed. Several studies have indicated that only a small percentage of retrievable IVC filters are removed, ranging between 20 and 50%, with the majority quoting rates close to 20%, while several device-related complications have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study from the Nationwide Inpatient Sample (NIS) conducted between 1998 and 2005, IVC filter placement increased by 157% for prophylactic purposes, compared to a 42% increase in placement for the treatment of VTE [3]. As more retrievable IVC filters are being used, familiarity with filter removal techniques has become essential.…”
Section: Introductionmentioning
confidence: 99%